Analysis of Organic Fertilizer Use in Improving Soil Quality and Agricultural Yields in Indonesia - Dewa Oka Suparwata; Fitriah Suryani Jamin (West Science Agro, 2024)
This research investigates the impact of organic fertilizer use on soil quality and agricultural yields in Indonesia through a qualitative analysis. Ten informants, including small-scale and large-scale farmers, agricultural experts, and environmentalists, provided insights into their perceptions and experiences. The study reveals diverse farmer perspectives, with small-scale farmers exhibiting limited awareness and large-scale farmers emphasizing long-term benefits. Organic fertilizers were found to positively influence soil quality, improving structure, water retention, and microbial activity. Crop-specific responses varied, highlighting the importance of considering regional agroecological conditions. Challenges such as access, affordability, and labor intensity were identified, countered by opportunities including government programs, cooperative farming, and consumer demand. Decision-making factors encompassed economic considerations, knowledge, environmental consciousness, and social influences. The synthesis underscores the need for tailored interventions, acknowledging the complexity of factors shaping the adoption of organic fertilizers in Indonesian agriculture.